Tape stripping and lipidomics reveal skin surface lipid abnormity in female melasma. (28th May 2021) - Xu, Jinhui; lu, Haojie; Luo, Haixin; Hu, Yebei; Chen, Yi; Xie, Bo; Du, Xiaohang; Hua, You; Song, Xiuzu
Abstract: The skin barrier of melasma is involved in the pathogenesis of melasma. Previous studies have shown that there are differences in the expression of epidermal lipid genes in melasma, but little is known about the epidermis lipid composition of melasma. Compared with the non‐lesional skin, the content of total lipids, phosphatidic acid, phosphatidylserine, and ceramide (Cer) increased significantly in the lesional skin. Multivariate data analysis indicated that 40 individual Cer lipid species were responsible for the discrimination. In terms of acyl chain length in Cer, the expressions of very long chain (VLC) (C20–C26) and ultra‐long chain (ULC) (>C26) increased significantly in the lesional skin. However, Cer[AH] had negative correlations with the activation of melanocytes in the lesional skin. Some lipid species had lower expression in lesional skin with high activation of melanocytes, as well as the high darkness. The epidermal thickness of lesional skin was higher compared with the non‐lesional skin. These results suggest that Cer increased significantly in the lesional skin of melasma, possibly as a compensatory mechanism to maintain skin barrier function. Between different groups of darkness and activation of melanocytes, the change of ceramides might have correlation with the pigmentation progress of melasma.